Investigation on Aluminium-Stainless Steel Dissimilar Weld Quality Using Different Filler Metals - L. H., Shah; Zetty Akhtar, Abd Malek; M., Ishak (Universiti Malaysia Pahang, 2013)
Aluminium-stainless steel dissimilar welding processes yields unwanted disadvantages on the weld joint due to the large difference between aluminium-stainless steel sheets melting points and nearly zero solid solubility between these two metals. Aluminium AA6061 and stainless steel SUS304 were lap-welded by using Metal Inert Gas (MIG) welding with aluminium filler ER5356 (Group 1) and stainless steel filler ER308LSi (Group 2). The effect of welding voltage and type of filler metals used on the weld joints were studied. The welding voltage had significant effect to the welding process, as higher voltage resulted in poorer appearance of the weld joint and leads to defects for both groups, such as porosity and incomplete fusion. The microstructure for Group 1 joints show enrichment of Si particle, which benefited the joint properties as it increases the strength of the metal. The stainless steel substrates that spread into the aluminium side are much more in volume for Group 1 compared to Group 2 joints. Meanwhile, the microstructure of Group 2 joints (using ER308LSi filler) consists of chromium carbide precipitation which yields high hardness value, but brittle structure. The hardness value of the welded seam in Group 1 and Group 2 ranges from 60 to 100 HV and 160 to 230 HV, respectively. The fracture in tensile test yielded the highest tensile strength of 104.4 MPa with aluminium fillers. The tensile strength of Group 1 joints ranging from 47.8 to 104.4 MPa were collectively higher compared to Group 2 joints, between 20.24 to 61.76 MPa. Based on the investigation throughout this study, it can be concluded that the welding voltage of 18 V and aluminium filler ER5356 is the optimum filler in joining dissimilar metal aluminium AA6061 and stainless steel SUS 304